Characterizing the Flow Regime in Brook Trout Incubation Habitats and Implications for Management in a Hydro‐Regulated River. (20th August 2022) - Slongo, Stephen A.; McLaren, Brian E.; Mackereth, Robert W.; Siddiqui, Sohail; Tyhuis, Raymond; Gibson, Daniel; Rennie, Michael D.
Abstract: The operation of dams, diversions, and power generation facilities unavoidably influence the ecological function of rivers. We evaluated vertical and horizontal hydraulic gradients and subsequent water temperature changes in the hyporheic zone of a spawning area for Brook Trout Salvelinus fontinalis in a managed Lake Superior tributary in Ontario, then conducted a laboratory‐based experiment to show the impact of cold shock during incubation on the timing of larval emergence and survival. Upwelling groundwater was observed at the spawning area during the monitoring period (October 28, 2016, to January 11, 2017); hyporheic water temperatures remained above 3.7°C, whereas ambient river temperature above the substrate fell to 1.5°C until water was released from the upstream control dam. After the release event, water level increased by 0.9 m over the spawning area, and within 24 h, vertical and horizontal flow gradients were reversed in the hyporheic zone; downwelling conditions were observed for 30 h between surface and hyporheic water 1.8 m below substrate, and hyporheic water temperature decreased in unison. Hyporheic temperatures at shallow inshore sites fell below 1°C for more than 53 h. In the laboratory, applying a worst‐case scenario of dam‐induced cold shock on Brook Trout redds using historic monitoring records (i.e., <1.0°C for 40 h), we found no appreciable effect on survival and development timing of incubating Brook Trout eggs compared with a control group. Survival from fertilization to hatching was high for both treatment and control groups (>90%) and lower from fertilization to emergence (55%). Overall, our results suggest that standard winter operating procedures on a Lake Superior tributary had little impact on Brook Trout egg survival and development time to hatching and emergence; however, our findings also suggest that staged winter discharges would lessen the reversal of flow in the hyporheic zone and the magnitude of temperature changes experienced at Brook Trout redds.